Gambaran Umum Kelainan Refraksi pada Pasien Anak Usia 6-12 Tahun di Divisi Refraksi dan Lensa Kontak Poliklinik Mata RSUP Sanglah Tahun 2014 - Putu Gian Mihartari; I Wayan Eka Sutyawan; AA Mas Putrawati Triningrat (Universitas Udayana, 2017)
Refractive error is one major cause of visual impairment worldwide that may affect various age groups and gender. This study aims to know the characteristics of pediatric patients aged 6-12 years with refractive error who came to Sanglah General Hospital in 2014. This study used secondary retrospective data from administration book at Eye Clinic Sanglah General Hospital and patient’s medical records that came to examined their eyes. All data that meet the criteria then analyzed descriptively. From 30 patients (60 eyes), most of them are male (53.3%) with ages 9-12 years old (63.3%). Myopia astigmatism compositus is the most common diagnosis (48.3%). Refractory errors also happened bilaterally in 96.7% patients. Uncorrected visual acuity examination had been done in all patients, >80% of them had visual acuity <6/6 and after corrected >70% of them had visual acuity <6/6. Around 83.3% of them categorized with normal vision or mild visual impairment. Anisometropia also found in 46.7% and the other 36.7% suspected amblyopia. Most pediatric patients with refractive errors in this study are male and the most common diagnosis is myopia astigmatism compositus which happen bilaterally in almost all patients. The results of this study could be applied as a basis data to other studies of refractive error in children. Keyword : pediatric, refractive errors, visual acuity, amblyopia, anisometropia